Paste composition for forming rear reflector layer of PERC type solar cell
A paste composition with a specific formulation of white pigments and glass powder addresses low infrared reflectivity and adhesion issues in PERC-type solar cells, improving efficiency and adhesion, resulting in enhanced performance.
Patent Information
- Application Number
- JP2020202279
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-12-04
- Publication Date
- 2025-02-05
- Estimated Expiration
- 2040-12-04
AI Technical Summary
Existing technologies for PERC-type solar cells have low reflectivity for infrared light (1000 to 1200 nm) and insufficient adhesion between the back reflective layer and adjacent layers, leading to suboptimal conversion efficiency and potential peeling issues.
A paste composition for forming a back reflective layer using a specific formulation of white pigments and glass powder, with a mass ratio of 95:5 to 80:20, applied between the silicon semiconductor substrate and the back electrode layer, enhancing reflectivity for both visible and infrared light and ensuring strong adhesion.
The composition achieves high reflectivity for both visible and infrared light, improving conversion efficiency and ensuring excellent adhesion with adjacent layers, thereby enhancing the performance of PERC-type solar cells.
Smart Images

Figure 0007627111000003 
Figure 0007627111000001 
Figure 0007627111000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a paste composition for forming a back reflective layer of a PERC type solar cell, and more particularly to a fired paste composition for forming a back reflective layer that reflects visible light and infrared light between a silicon semiconductor substrate and a back electrode layer of a crystalline PERC type solar cell. [Background technology]
[0002] Various research projects are being conducted to improve the conversion efficiency (power generation efficiency) and reliability of crystalline solar cells. Among these, PERC (Passivated emitter and rear cell) solar cells, which have a passivation film made of silicon nitride, silicon oxide, aluminum oxide, etc. on the back side of a silicon semiconductor substrate, are considered to be promising in terms of high conversion efficiency.
[0003] In order to increase the rear reflectance of incident light in a solar cell, various structures and reflective layers have been devised as described below.
[0004] For example, Patent Document 1 discloses a solar cell, and describes that the thickness of the silicon nitride film formed on the back surface of a silicon single crystal substrate is limited to a specific range. Patent Document 2 discloses a polyimide resin composition for forming a back surface reflective layer of a solar cell and a method for forming a back surface reflective layer of a solar cell using the same, and describes the use of a resin composition containing an organic solvent, a polyimide resin dissolved in the organic solvent, and light-reflective particles (particularly white pigment particles) dispersed in the organic solvent as the polyimide resin composition for forming the back surface reflective layer of a BSF type cell. In addition, Patent Document 3 discloses a composition for forming a reflective film and a reflective substrate using the composition, and describes the use of a composition (fired paste) containing a white pigment, glass, and resin as the composition for forming a reflective film, in which the glass contains zinc borosilicate glass. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2008-172279 A [Patent Document 2] JP 2012-69592 A [Patent Document 3] JP 2012-140479 A Summary of the Invention [Problem to be solved by the invention]
[0006] However, the technologies described in Patent Documents 1 and 3 have low reflectance of infrared light (1000 to 1200 nm), and do not achieve sufficient improvement in conversion efficiency. In addition, in the technology described in Patent Document 2, the BSF type cell has a significantly inferior conversion efficiency compared to a PERC type cell equipped with a passivation film, and even if it is used as is in a PERC type cell, sufficient adhesion with the passivation film cannot be obtained, and there is a risk of interfacial coagulation and peeling occurring between the passivation film and the white pigment particles (e.g., TiO2) or between TiO2 and the electrode.
[0007] Therefore, an object of the present invention is to provide a fired paste composition that can form a back reflective layer between the silicon semiconductor substrate and the back electrode layer of a PERC type solar cell, which can reflect not only visible light but also infrared light (1000 to 1200 nm) and has excellent adhesion to adjacent layers (passivation film and back electrode layer). [Means for solving the problem]
[0008] As a result of intensive research into achieving the above-mentioned object, the inventors have found that the above-mentioned object can be achieved when a back reflective layer is formed using a fired paste composition having a specific composition, and have thus completed the present invention.
[0009] That is, the present invention relates to the following paste composition for forming a back reflector layer of a PERC type solar cell. 1. A bakeable paste composition for forming a back reflector layer between a silicon semiconductor substrate and a back electrode layer of a PERC type solar cell, comprising: Average particle size is 0.5μm or more 3.1 The present invention comprises a white pigment having a particle size of 0.1 μm or less and a white and / or colorless transparent glass powder, and the total mass of the white pigment and the glass powder is 60 mass% or more. 75 % by mass or less, and the mass ratio of the white pigment to the glass powder is in the range of 95:5 to 80:20. A paste composition for forming a rear surface reflective layer, comprising: 2. The paste composition for forming a rear reflection layer according to item 1, wherein the white pigment is at least one selected from the group consisting of aluminum oxide particles, titanium oxide particles, magnesium oxide particles, selenium oxide particles, zinc oxide particles, barium sulfate particles, calcium sulfate particles, calcium carbonate particles, and barium carbonate particles. 3. A paste composition for forming a rear reflector according to item 1 or 2, wherein the glass powder contains at least one element selected from the group consisting of lead (Pb), bismuth (Bi), vanadium (V), boron (B), silicon (Si), tin (Sn), phosphorus (P), and zinc (Zn). Effect of the Invention
[0010] According to the paste composition for forming a back surface reflector of a PERC type solar cell of the present invention, by applying and firing the paste composition, a back surface reflector layer can be formed between a silicon semiconductor substrate and a back surface electrode layer, which can reflect not only visible light but also infrared light (1000 to 1200 nm) and has excellent adhesion to adjacent layers (passivation film and back surface electrode layer). [Brief description of the drawings]
[0011] [Figure 1] 1A and 1B are diagrams showing schematic cross-sectional structures of PERC solar cells, in which (A) is an example of a conventional PERC solar cell that does not have a back reflector layer, and (B) is an example of a PERC solar cell of the present invention that has a back reflector layer. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] The paste composition for forming a back reflector layer of a PERC solar cell of the present invention will be described in detail below. In this specification, the range indicated by "to" means "above or below" unless otherwise specified. In addition, regarding the positional relationship, the light receiving surface (side) of a PERC solar cell is referred to as the "front surface (side)" or the "upper surface (side)", and the surface (side) opposite to the light receiving surface is referred to as the "rear surface (side)" or the "lower surface (side)".
[0013] First, an example of the structure of a PERC type solar cell will be described.
[0014] 1. PERC solar cell Fig. 1(A) is a schematic diagram of a typical cross-sectional structure of a PERC type solar cell. A PERC type solar cell can include, as components, a silicon semiconductor substrate 1, an n-type impurity layer 2, an anti-reflective film (passivation film) 3, a grid electrode 4, a back electrode layer 5, an alloy layer 6, and a p+ layer 7. The back electrode layer 5 and the alloy layer 6 are collectively referred to as a back electrode 8.
[0015] FIG. 1(B), which shows an example of a PERC type solar cell of the present invention, is characterized in that in FIG. 1(A), a rear reflector layer 9 is formed by firing between the passivation film 3 on the rear surface of the silicon semiconductor substrate and the rear electrode layer 5.
[0016] As a result, the PERC solar cell of the present invention, which is equipped with a back surface reflective layer formed from the paste composition for forming a back surface reflective layer of the present invention, can reflect not only visible light but also infrared light (1000 to 1200 nm) of incident light, and can achieve a higher conversion efficiency than conventional products. In addition, the PERC solar cell of the present invention also has excellent adhesion between the back surface reflective layer and its adjacent layers (passivation film and back surface electrode layer).
[0017] The silicon semiconductor substrate 1 is not particularly limited, and for example, a p-type silicon substrate having a thickness of 180 to 250 μm is used.
[0018] N-type impurity layer 2 is provided on the light-receiving surface side of silicon semiconductor substrate 1. N-type impurity layer 2 has a thickness of, for example, 0.3 to 0.6 μm.
[0019] The anti-reflection film 3 and the grid electrode 4 are provided on the surface of the n-type impurity layer 2. The anti-reflection film 3 is formed of, for example, a silicon nitride film and is also called a passivation film. The anti-reflection film 3 acts as a so-called passivation film, thereby suppressing the recombination of electrons on the surface of the silicon semiconductor substrate 1, and as a result, makes it possible to reduce the recombination rate of generated carriers. This increases the conversion efficiency of the PERC solar cell.
[0020] An anti-reflection film (passivation film) 3 is also provided on the back surface of the silicon semiconductor substrate 1, that is, on the surface opposite to the light-receiving surface. A contact hole (opening) is formed on the back surface of the silicon semiconductor substrate 1, penetrating the anti-reflection film (passivation film) 3 on the back surface and formed so as to remove a part of the back surface of the silicon semiconductor substrate 1. The method of forming the contact hole is not limited, but a method called LCO (Laser contact opening) in which an opening is formed using laser irradiation or the like is generally used.
[0021] The back electrode layer 5 is formed so as to contact the silicon semiconductor substrate 1 through the contact hole. The back electrode layer 5 is generally a member formed of a paste composition containing conductive powder such as aluminum powder (which may contain aluminum alloy powder) and is formed into a predetermined pattern shape. As shown in Figs. 1(A) and (B), the back electrode layer 5 may be formed so as to cover the entire back surface of the PERC solar cell, or may be formed so as to cover the contact hole and its vicinity. The main component of the back electrode layer 5 is generally aluminum, so the back electrode layer 5 is generally an aluminum electrode layer.
[0022] The back electrode layer 5 is formed, for example, by applying an aluminum paste composition in a predetermined pattern shape and firing the composition. The application method is not particularly limited, and examples thereof include known methods such as screen printing. The aluminum paste composition is applied, dried as necessary, and then fired for a short time at a temperature exceeding the melting point of aluminum (about 660°C) to form the back electrode layer 5. When applying the paste composition for forming a back reflector of the present invention, the paste composition for forming a back reflector of the present invention is applied to the back surface of a passivation film on the back surface of a silicon semiconductor substrate, and then a contact hole is formed, followed by applying the aluminum paste composition and firing the resulting product.
[0023] In the present invention, the firing temperature may be any temperature that exceeds the melting point of aluminum (about 660° C.), and is preferably about 750 to 950° C., and more preferably about 780 to 900° C. The firing time can be appropriately set according to the firing temperature within a range in which the desired back surface reflective layer 9 and back surface electrode layer 5 are formed.
[0024] By firing in this manner, aluminum contained in the aluminum paste composition diffuses into the silicon semiconductor substrate 1. As a result, an aluminum-silicon (Al-Si) alloy layer (alloy layer 6) is formed between the back electrode layer 5 and the silicon semiconductor substrate 1, and at the same time, a p+ layer 7 is formed as an impurity layer by the diffusion of aluminum atoms. In addition, a back reflector layer 9 is formed by firing.
[0025] The p+ layer 7 can provide the effect of preventing the recombination of electrons and improving the collection efficiency of generated carriers, that is, the so-called back surface field (BSF) effect.
[0026] 2. Paste composition for forming rear reflective layer of the present invention The paste composition for forming a rear reflector of the present invention (also referred to as the "paste composition of the present invention") is a fired paste composition for forming a rear reflector between a silicon semiconductor substrate and a rear electrode layer of a PERC type solar cell, The composition is characterized in that it contains a white pigment having an average particle size of 0.5 μm or more and 3.5 μm or less, and a white and / or colorless and transparent glass powder, the total mass of the white pigment and the glass powder is in the range of 60 mass % or more and 80 mass % or less, and the mass ratio of the white pigment to the glass powder is in the range of 98:2 to 60:40.
[0027] According to the paste composition of the present invention, by applying and baking the paste composition, a back surface reflective layer can be formed between a silicon semiconductor substrate and a back surface electrode layer, which can reflect not only visible light but also infrared light (1000 to 1200 nm) and has excellent adhesion to adjacent layers (passivation film and back surface electrode layer).
[0028] The paste composition of the present invention contains, as its constituent components, at least the white pigment, the glass powder, and an organic vehicle described below. The constituent components of the paste composition of the present invention will be described below.
[0029] (White pigment) The white pigment used in the present invention has an average particle size of 0.5 μm or more and 3.5 μm or less. By having the average particle size in the above range, it is possible to exhibit high reflectivity not only for visible light but also for infrared light. This makes it possible to efficiently reflect incident light transmitted through the silicon semiconductor substrate and increase the conversion efficiency of the PERC type solar cell.
[0030] The above-mentioned average particle size refers to the number average particle size. The white pigment (inorganic particles) in the paste composition of the present invention exists in the form of primary particles in which the aggregates are completely loosened, and in the form of secondary particles in which a plurality of primary particles are aggregated. Here, the particle size of the inorganic particles in the paste composition refers to the particle size of the primary particles that are not aggregated, and refers to the particle size of the aggregates in which the primary particles are aggregated. As a method for measuring the average particle size of the inorganic particles in the paste composition, a method of directly observing the particles with a SEM (scanning electron microscope) and calculating the number average particle size can be mentioned.
[0031] Specific examples of the white pigment include at least one selected from the group consisting of aluminum oxide particles, titanium oxide particles, magnesium oxide particles, selenium oxide particles, zinc oxide particles, barium sulfate particles, calcium sulfate particles, calcium carbonate particles, and barium carbonate particles. Among these, at least one of aluminum oxide and titanium oxide (particularly titanium dioxide) is preferred in terms of optical properties such as refractive index, thermal expansion coefficient, environmental resistance, and the like. Note that, although the white pigment is an inorganic particle, as is clear to those skilled in the art, the white pigment is distinguished from the glass powder described below both in terms of components and concepts.
[0032] The shape of the white pigment is not particularly limited, and any suitable shape such as spherical, elliptical, scaly, or irregular may be used.
[0033] (Glass powder) The glass powder in the present invention is white and / or colorless and transparent glass powder. In the paste composition of the present invention, the glass powder imparts adhesion between the white pigments, between the silicon semiconductor substrate and the white pigment, and further between the white pigment and the back electrode layer.
[0034] The glass powder preferably contains at least one selected from the group consisting of lead (Pb), bismuth (Bi), vanadium (V), boron (B), silicon (Si), tin (Sn), phosphorus (P), and zinc (Zn). Specifically, a glass powder containing lead, or a lead-free glass powder such as a bismuth-based, vanadium-based, tin-phosphorus-based, zinc borosilicate-based, or alkali borosilicate-based glass powder can be used. In particular, in consideration of the effects on the human body, it is desirable to use a lead-free glass powder.
[0035] The softening point of the glass powder is preferably not more than 650° C. Furthermore, the volume average particle diameter D50 of the glass particles constituting the glass powder is preferably 1 to 3 μm.
[0036] In the paste composition of the present invention, the mass ratio of the white pigment to the glass powder is in the range of 98:2 to 60:40, and preferably in the range of 95:5 to 80:20. By setting the mass ratio in this range, excellent adhesion between the rear surface reflective layer and adjacent layers (passivation film and rear surface electrode layer) can be obtained while ensuring high reflectance of visible light and infrared light.
[0037] (Organic Vehicle) The paste composition of the present invention further contains an organic vehicle as a binder. As the organic vehicle, a material in which various additives and / or resins are dissolved in a solvent can be used. Alternatively, the organic vehicle may be a resin itself without containing a solvent.
[0038] As the above-mentioned solvent, known types can be used, and specifically, at least one type selected from the group consisting of diethylene glycol monobutyl ether, diethylene glycol monobutyl ether acetate, and dipropylene glycol monomethyl ether can be mentioned.
[0039] Examples of various additives include one or more of antioxidants, corrosion inhibitors, defoamers, thickeners, tackifiers, coupling agents, electrostatic agents, polymerization inhibitors, thixotropic agents, antisettling agents, etc. Specifically, polyethylene glycol ester compounds, polyethylene glycol ether compounds, polyoxyethylene sorbitan ester compounds, sorbitan alkyl ester compounds, aliphatic polycarboxylic acid compounds, phosphate ester compounds, amide amine salts of polyester acids, oxidized polyethylene compounds, fatty acid amide waxes, etc. can be used.
[0040] As the resin, known types can be used, and one or more types selected from the following can be used in combination: thermosetting resins such as ethyl cellulose, nitrocellulose, polyvinyl butyral, phenolic resins, melamine resins, urea resins, xylene resins, alkyd resins, unsaturated polyester resins, acrylic resins, polyimide resins, furan resins, urethane resins, isocyanate compounds, and cyanate compounds; polyethylene, polypropylene, polystyrene, ABS resins, polymethyl methacrylate, polyvinyl chloride, polyvinylidene chloride, polyvinyl acetate, polyvinyl alcohol, polyacetal, polycarbonate, polyethylene terephthalate, polybutylene terephthalate, polyphenylene oxide, polysulfone, polyimide, polyether sulfone, polyarylate, polyether ether ketone, polyethylene 4-fluoroethylene, and silicone resins.
[0041] The ratio of the resin, solvent, and various additives contained in the organic vehicle can be adjusted as desired, and can be, for example, the same component ratio as that of known organic vehicles.
[0042] In the paste composition of the present invention, the total mass of the white pigment and the glass powder is in the range of 60% by mass to 80% by mass, preferably 75% by mass to 80% by mass, whereby excellent adhesion between the rear surface reflective layer and adjacent layers (passivation film and rear surface electrode layer) can be obtained while ensuring high reflectance of visible light and infrared light. EXAMPLES
[0043] The present invention will be specifically described below with reference to examples and comparative examples, but the present invention is not limited to the examples. It should be noted that Examples 1, 2, 5 and 6 are all reference examples.
[0044] Example 1 A paste composition for forming a rear surface reflection layer was prepared by mixing 36 parts by mass of spherical aluminum oxide powder having an average particle size of 0.5 μm, which is a typical white pigment, 24 parts by mass of white boric acid-based glass powder represented by the formula B2O3-Bi2O3-SrO-BaO-Sb2O3 = 40 / 40 / 10 / 5 / 5 (mol %), and 40 parts by mass of a resin solution in which ethyl cellulose was dissolved in butyl diglycol using a known dispersing device (disper).
[0045] A PERC solar cell for evaluation was fabricated using the following procedure. First, a silicon semiconductor substrate with a 180 μm thick passivation film was prepared, which had a top passivation film and a back passivation film (silicon nitride film) as shown in Figure 1. The silicon semiconductor substrate had a resistance of 3 Ω·cm and was a well-known back passivation type single crystal.
[0046] Next, a paste composition for forming a back surface reflection layer was printed on the entire back surface of the silicon semiconductor substrate using a screen printer so as to give 0.5 to 0.6 g / cell, and then dried at 100° C. for 10 minutes.
[0047] Next, a contact hole having a width of 50 μm and a depth of 1 μm relative to the silicon semiconductor substrate was formed on the back surface of the silicon semiconductor substrate by penetrating the coating of the dried paste composition for forming a back surface reflection layer using a YAG laser with a wavelength of 532 nm as a laser oscillator.
[0048] Next, a known aluminum paste was printed with a screen printer at 1.0 to 1.1 g / cell to cover the entire back surface (the surface on which the contact holes were formed), and then dried. Next, an Ag paste prepared by a known technique was printed on the light-receiving surface.
[0049] Next, the substrate was sintered in an infrared belt furnace set at 800°C. This sintering process formed a back electrode layer, and aluminum diffused into the silicon semiconductor substrate during the sintering process, forming an Al-Si alloy layer between the back electrode layer and the silicon semiconductor substrate, while at the same time forming a p+ layer (BSF layer) as an impurity layer due to the diffusion of aluminum atoms. This resulted in the fabrication of a PERC solar cell for evaluation.
[0050] In the evaluation of the obtained solar cell, Jsc was 37.95mA / cm 2 The above values indicate that the rear reflective layer has improved the reflectance of visible light and infrared light. When infrared light with a wavelength of 1000 to 1200 nm was incident on the light-receiving surface side using an integrating sphere spectrophotometer, the reflectance was measured to be 50% or more.
[0051] Adhesion was evaluated by attaching a 3cm length of mending tape (12mm wide, manufactured by 3M) to the surface of the back electrode layer formed on the silicon semiconductor substrate, then vigorously peeling the tape off at a 45 degree angle to the silicon semiconductor substrate, and calculating the ratio of the total area of the aluminum-adhered area to the area of the original mending tape using analysis software capable of binary processing. All adhesion evaluations were performed by the same person with the same posture, angle, force, and constant speed. Mending tape with no aluminum attached at all was rated A (good), and mending tape with even a small amount of aluminum attached was rated B (bad).
[0052] The overall evaluation is Jsc of 37.95mA / cm 2 Those that satisfied the above criteria (i.e., improved reflectance of visible light and infrared light was achieved by the rear reflective layer) and the adhesion evaluation were rated as A (good), and those that did not satisfy any of the criteria were rated as B (poor).
[0053] Details of each example are shown in Table 1.
[0054] Example 2 A paste composition for forming a rear reflector layer was prepared and evaluated in the same manner as in Example 1, except that 42 parts by mass of spherical aluminum oxide powder having an average particle size of 0.8 μm and 18 parts by mass of white boric acid-based glass powder were used.
[0055] Example 3 A paste composition for forming a rear reflector layer was prepared and evaluated in the same manner as in Example 1, except that 48 parts by mass of rod-shaped aluminum oxide powder having an average particle size of 1.0 μm and 12 parts by mass of white boric acid-based glass powder were used.
[0056] Example 4 A paste composition for forming a rear reflector layer was prepared and evaluated in the same manner as in Example 1, except that 48 parts by mass of spherical aluminum oxide powder having an average particle size of 2.0 μm and 12 parts by mass of white boric acid-based glass powder were used.
[0057] Example 5 A paste composition for forming a rear surface reflection layer was prepared and evaluated in the same manner as in Example 1, except that 42 parts by mass of spherical titanium dioxide powder having an average particle size of 0.5 μm, 28 parts by mass of white boric acid-based glass powder, and 30 parts by mass of the resin solution were used.
[0058] Example 6 A paste composition for forming a rear reflector layer was prepared and evaluated in the same manner as in Example 5, except that 49 parts by mass of spherical titanium dioxide powder having an average particle size of 1.0 μm and 21 parts by mass of white boric acid-based glass powder were used.
[0059] Example 7 A paste composition for forming a rear reflector layer was prepared and evaluated in the same manner as in Example 5, except that 56 parts by mass of spherical titanium dioxide powder having an average particle size of 2.2 μm and 14 parts by mass of white boric acid-based glass powder were used.
[0060] Example 8 A paste composition for forming a rear reflector layer was prepared and evaluated in the same manner as in Example 5, except that 56 parts by mass of spherical titanium dioxide powder having an average particle size of 3.1 μm and 14 parts by mass of white boric acid-based glass powder were used.
[0061] Comparative Example 1 A paste composition for forming a rear reflector layer was prepared and evaluated in the same manner as in Example 1, except that 36 parts by mass of spherical titanium dioxide powder having an average particle size of 0.02 μm and 24 parts by mass of white boric acid-based glass powder were used.
[0062] Details of each comparative example are shown in Table 2.
[0063] Comparative Example 2 A paste composition for forming a rear reflector layer was prepared and evaluated in the same manner as in Example 1, except that 36 parts by mass of spherical titanium dioxide powder having an average particle size of 0.3 μm and 24 parts by mass of white boric acid-based glass powder were used.
[0064] Comparative Example 3 A paste composition for forming a rear surface reflection layer was prepared and evaluated in the same manner as in Example 1, except that 35 parts by mass of spherical titanium dioxide powder having an average particle size of 0.5 μm, 24 parts by mass of white boric acid-based glass powder, and 41 parts by mass of the resin solution were used.
[0065] Comparative Example 4 A paste composition for forming a rear surface reflection layer was prepared and evaluated in the same manner as in Example 1, except that 33 parts by mass of spherical titanium dioxide powder having an average particle size of 0.5 μm, 22 parts by mass of white boric acid-based glass powder, and 45 parts by mass of the resin solution were used.
[0066] Comparative Example 5 A paste composition for forming a rear reflector was prepared and evaluated in the same manner as in Example 1, except that 30 parts by mass of spherical titanium dioxide powder having an average particle size of 1.0 μm, 30 parts by mass of white boric acid-based glass powder, and 50 parts by mass of the resin solution were used.
[0067] Comparative Example 6 A paste composition for forming a rear reflector was prepared and evaluated in the same manner as in Example 1, except that 59 parts by mass of spherical titanium dioxide powder having an average particle size of 1.0 μm, 1 part by mass of white boric acid-based glass powder, and 40 parts by mass of the resin solution were used.
[0068] Comparative Example 7 A paste composition for forming a rear surface reflection layer was prepared and evaluated in the same manner as in Example 1, except that 56 parts by mass of spherical titanium dioxide powder having an average particle size of 3.6 μm, 14 parts by mass of white boric acid-based glass powder, and 30 parts by mass of the resin solution were used.
[0069] Comparative Example 8 A paste composition for forming a rear reflector was prepared and evaluated in the same manner as in Example 1, except that 48 parts by mass of spherical titanium dioxide powder having an average particle size of 1.0 μm, 12 parts by mass of black vanadium glass powder, and 40 parts by mass of the resin solution were used.
[0070] Comparative Example 9 Evaluation was carried out in the same manner as in Example 1, except that the back reflective layer was not formed.
[0071] Comparative Example 10 Similar to the technology described in Patent Document 2, a known aluminum paste was printed on the back surface of a BSF-type silicon single crystal substrate not including a passivation film as an evaluation substrate, a known silver paste was printed on the top surface of the silicon single crystal substrate, and the substrate was fired. After that, the aluminum sintered layer and the Al-Si alloy layer on the back surface were removed by hydrochloric acid etching to prepare a solar cell silicon substrate with an exposed BSF layer.
[0072] A paste composition for forming a rear reflector was prepared in the same manner as in Example 1 using 40 parts by mass of spherical titanium dioxide powder having an average particle size of 0.3 μm and 357 parts by mass of a 28% polyimide resin solution. The paste composition was applied in a predetermined pattern to the rear surface of the solar cell silicon substrate and dried at 250° C. for 30 minutes. Finally, a rear electrode was formed by aluminum deposition, and evaluation was performed.
[0073] Comparative Example 11 The paste composition for forming a rear reflector prepared in Comparative Example 10 was applied to the PERC solar cell for evaluation in Example 1, and an evaluation was performed.
[0074] [Table 1]
[0075] [Table 2]
[0076] As shown in Table 1, by using the paste composition for forming a back surface reflector of the present invention to form a back surface reflector between the silicon semiconductor substrate and the back surface electrode layer of a PERC type solar cell, it is possible to obtain high reflectance not only for visible light but also for infrared light of 1000 to 1200 nm, and it is also found that adhesion to adjacent layers (passivation film and back surface electrode layer) is good. [Explanation of symbols]
[0077] 1. Silicon semiconductor substrate 2.N-type impurity layer 3.Anti-reflective coating (passivation coating) 4. Grid Electrode 5.Back electrode layer 6.Alloy layer 7.p+ layer 8. Back electrode 9. Back reflective layer
Claims
1. A fired paste composition for forming a back reflector layer between a silicon semiconductor substrate and a back electrode layer of a PERC type solar cell, comprising: The present invention contains a white pigment having an average particle size of 0.5 μm or more and 3.1 μm or less, and a white and / or colorless and transparent glass powder, the total mass of the white pigment and the glass powder is in the range of 60 mass% or more and 75 mass% or less, and the mass ratio of the white pigment to the glass powder is in the range of 95:5 to 80:
20. A paste composition for forming a rear surface reflective layer, comprising:
2. 2. The paste composition for forming a rear surface reflection layer according to claim 1, wherein the white pigment is at least one selected from the group consisting of aluminum oxide particles, titanium oxide particles, magnesium oxide particles, selenium oxide particles, zinc oxide particles, barium sulfate particles, calcium sulfate particles, calcium carbonate particles, and barium carbonate particles.
3. 3. The paste composition for forming a rear reflector according to claim 1, wherein the glass powder contains at least one element selected from the group consisting of lead (Pb), bismuth (Bi), vanadium (V), boron (B), silicon (Si), tin (Sn), phosphorus (P), and zinc (Zn).
Citation Information
Patent Citations
Back film structure for improving conversion efficiency of single-sided PERC battery
CN211654848U
Wafer solar cell, solar module and method for manufacturing the wafer solar cell
DE102019114498A1
Low melting point glass composition
JP2001031446A
Solar cell
JP2008172279A
Acid-resistant lead-free glass composition and glass paste
JP2008189532A